Expression Profiling Elucidates a Molecular Gene Signature for Pulmonary Hypertension in Sarcoidosis. (1st December 2016) - Singla, Sunit; Zhou, Tong; Javaid, Kamran; Abbasi, Taimur; Casanova, Nancy; Zhang, Wei; Ma, Shwu‐Fan; Wade, Michael S.; Noth, Imre; Sweiss, Nadera J.; Garcia, Joe G. N.; Machado, Roberto F.
Abstract : Pulmonary hypertension (PH), when it complicates sarcoidosis, carries a poor prognosis, in part because it is difficult to detect early in patients with worsening respiratory symptoms. Pathogenesis of sarcoidosis occurs via incompletely characterized mechanisms that are distinct from the mechanisms of pulmonary vascular remodeling well known to occur in conjunction with other chronic lung diseases. To address the need for a biomarker to aid in early detection as well as the gap in knowledge regarding the mechanisms of PH in sarcoidosis, we used genome‐wide peripheral blood gene expression analysis and identified an 18‐gene signature capable of distinguishing sarcoidosis patients with PH ( n = 8), sarcoidosis patients without PH ( n = 17), and healthy controls ( n = 45). The discriminative accuracy of this 18‐gene signature was 100% in separating sarcoidosis patients with PH from those without it. If validated in a large replicate cohort, this signature could potentially be used as a diagnostic molecular biomarker for sarcoidosis‐associated PH.